Integrated Pest Management Protocols for Space-Based Bioregenerative Life Support Systems - Schuerger, Andrew C. (Frontiers in Astronomy and Space Sciences, 2021)
Human missions to the Moon and Mars will necessarily increase in both duration and complexity over the coming decades. In the past, short-term sortie mission to low-Earth orbit (LEO) or the Moon (e.g., Apollo) utilized physiochemical life support systems for the crews. However, as the spatial and temporal durations of crewed missions to other planetary bodies increase, physiochemical life support systems become burdened with the requirement of frequent resupply missions. Bioregenerative life support systems (BLSS) have been proposed to replace much of the resupply required of physiochemical systems with modules that can regenerate water, oxygen, and food stocks with plant-based biological production systems. In order to protect the stability and productivity of BLSS modules (i.e., small scale units) or habitats (i.e., large scale systems), an integrated pest management (IPM) program is required to prevent, mitigate, and eliminate both insect pests and disease outbreaks in space-based plant-growing systems. A first-order BLSS IPM program is outlined herein that summarizes a collection of protocols that are similar to those used in field and greenhouse agricultural systems. However, the space environment offers numerous unusual stresses to plants, and thus, unique space-based IPM protocols will have to be developed. In general, successful operation of space-based BLSS units will be guided by IPM protocols that (i) should be established early in the mission design phase to be effective, (ii) will be dynamic in nature changing both spatially and temporally depending on the successional processes afoot within the crewed spacecraft, plant-growing systems, and through time; and (iii) can prevent insect/phytopathology outbreaks at very high levels that can approach 100% if properly implemented.